2021
DOI: 10.3390/ijfs9010014
|View full text |Cite
|
Sign up to set email alerts
|

Role of ICT Investment and Diffusion in the Economic Growth: A Threshold Approach for the Empirical Evidence from Pakistan

Abstract: This study investigates the role of Information and Communication Technologies (ICT) investment and diffusion on Pakistan’s economic growth by proposing the threshold level of ICT investment. At our proposed level, the ICT imports significantly enhance the intermediate inputs to capital goods, ultimately enhancing economic growth. For this empirical investigation, we use the maximum available data on technological innovation and investment, ranging from 2003 to 2018. Incorporating the structural breaks, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…However, in the extant literature, furthermost of the empirical studies on the subject have intensive on industrialized and emerging economies from both single country and panel or cross-country perspectives. The single country perspective studies include, but are not limited to those conducted for Brazil (Jung & López-Bazo, 2019), Greece (Tsakanikas, Dimas, & Stamopoulos, 2021), Italy (Daniele, 2006), USA (Whitacre, Gallardo, & Strover, 2014), Japan (Ishida, 2015), Türkiye (Iscan, 2012), Aus-Journal of Human Resource and Sustainability Studies tralia (Gretton et al, 2002), Singapore (Vu, Hanafizadeh, & Bohlin, 2020), India (Reddy & Mehjabeen, 2019;Rahman et al, 2021), Pakistan (Rahman et al, 2021) and UAE (Omran et al, 2013). Similarly, most empirical studies have looked at it from a panel or cross-country perspective.…”
Section: Literature Review and Forming Of Hypothesismentioning
confidence: 99%
“…However, in the extant literature, furthermost of the empirical studies on the subject have intensive on industrialized and emerging economies from both single country and panel or cross-country perspectives. The single country perspective studies include, but are not limited to those conducted for Brazil (Jung & López-Bazo, 2019), Greece (Tsakanikas, Dimas, & Stamopoulos, 2021), Italy (Daniele, 2006), USA (Whitacre, Gallardo, & Strover, 2014), Japan (Ishida, 2015), Türkiye (Iscan, 2012), Aus-Journal of Human Resource and Sustainability Studies tralia (Gretton et al, 2002), Singapore (Vu, Hanafizadeh, & Bohlin, 2020), India (Reddy & Mehjabeen, 2019;Rahman et al, 2021), Pakistan (Rahman et al, 2021) and UAE (Omran et al, 2013). Similarly, most empirical studies have looked at it from a panel or cross-country perspective.…”
Section: Literature Review and Forming Of Hypothesismentioning
confidence: 99%
“…The development of telecommunication infrastructure construction to some extent drives the R&D of telecommunication technology [15,16]. In the history of the development of the telecommunications industry, electronic equipment companies often occupy the commanding heights of the telecommunications industry chain by mastering telecommunication technology patents [17]. In telecommunication infrastructure construction, the R&D of telecommunication technology must have a high level of innovation to effectively support it.…”
Section: Analysis Of the Impact Of Telecommunication Infrastructure C...mentioning
confidence: 99%
“…As a result, the rapid and progressive shift to online education caught most institutions, lecturers, and students off guard. Rahman et al (2021) have suggested that eligibility in online education has exploded in media online learning over the last two centuries since the media online learning style refers to a wide population of learners with a range of demands that traditional face-toface sessions are unable to provide. For self-regulated learners, online learning has proven to be very successful.…”
Section: Mediating Role Of the Forced Shift To Media Online Learningmentioning
confidence: 99%